A temperature-resistant and salt-resistant oil well cement slurry fluid loss agent and a preparation method thereof

CN122685809APending Publication Date: 2026-09-04HENAN XINXING BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610827894.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

然而,在温度高于180℃的条件下,常规线性共聚物存在以下缺陷:分子链水化膜变薄,导致聚合物链卷曲、流体动力学体积减小,滤失控制能力急剧下降;在饱和盐水环境中,高浓度钠离子压缩阴离子型聚合物分子链的双电层,仅含阴离子基团的聚合物因电荷屏蔽效应导致吸附能力显著衰减;现有技术中引入纳米材料的方案多采用物理共混的方式,纳米材料易在水泥浆碱性环境中团聚,分散稳定性差,难以持续发挥作用

Benefits of technology

磺酸类单体参与聚合物主链形成,提供抗盐性能;酰胺类单体参与聚合物主链形成,提高聚合物与水泥颗粒的结合能力;内酰胺类单体参与聚合物主链形成,提高聚合物的热稳定性;羟基酯类单体参与聚合物主链形成,增强聚合物与水泥颗粒的相互作用;两性离子单体甲基丙烯酰氧乙基磺基甜菜碱参与聚合物主链形成,其分子结构中的正负电荷基团具有反聚电解质效应,在高盐环境中分子链反而伸展,显著提升聚合物的流体动力学体积和抗盐吸附能力;羧基化纳米纤维素以一维刚性棒状结构均匀分散于聚合物体系中,可填充滤饼孔隙提高致密性;其表面大量羧基可同时与水泥颗粒和聚合物链形成氢键与静电作用,增强体系稳定性和高温下的结构完整性;乙烯基硅烷杂化交联剂通过乙烯基参与自由基聚合引入聚合物主链,其水解产生的硅醇基团进一步发生缩合反应形成Si-O-Si无机交联键,最终构建有机-无机杂化三维网络结构;氧化还原引发体系引发单体聚合反应;链转移剂调控聚合物的分子量;pH调节剂调节体系pH至6.5~7.5,保证聚合反应顺利进行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent and its preparation method. Based on 100 parts by weight of deionized water, the raw materials for preparing the fluid loss reducing agent include: 7-12 parts of sulfonic acid monomers, 5-9 parts of amide monomers, 2-5 parts of lactam monomers, 1-3 parts of hydroxy ester monomers, 0.8-2.5 parts of zwitterionic monomers, 0.2-0.8 parts of carboxylated nanocellulose, 0.1-0.5 parts of vinylsilane hybrid crosslinking agent, 0.4-0.8 parts of redox initiation system, and 0.05-0.2 parts of chain transfer agent. The raw materials for preparing the fluid loss reducing agent also include a pH adjuster to adjust the pH of the system to 6.5-7.5. This invention introduces lactam monomers to improve the thermal stability of the polymer backbone and inhibit molecular chain breakage at high temperatures; introduces zwitterionic monomers to alleviate the charge shielding effect in high-salt environments, so that the polymer still maintains good solubility and adsorption capacity in saturated salt water; and sulfonic acid, amide and hydroxy ester monomers work synergistically to balance salt resistance and cement particle adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil and gas well cementing engineering materials technology, specifically to a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent and its preparation method. Background Technology

[0002] In oil and gas well cementing operations, cement slurry can be lost to permeable formations under pressure differential, potentially leading to uncontrolled slurry thickening time, annular bridging, decreased cementing quality, or even cementing accidents. With increased exploration and development of deep and ultra-deep oil and gas resources and higher drilling rates of salt-gypsum and high-pressure brine layers, the cementing environment is characterized by a combination of high temperature and high salinity.

[0003] Existing polymer-based water loss control agents mostly use 2-acrylamide-2-methylpropanesulfonic acid and N,N-dimethylacrylamide as the main comonomers, providing salt resistance through sulfonic acid groups. However, under conditions above 180°C, conventional linear copolymers have the following defects: the molecular chain hydration film thins, leading to polymer chain curling, reduced hydrodynamic volume, and a sharp decline in filtration control capacity; in saturated brine environments, high concentrations of sodium ions compress the electric double layer of anionic polymer molecular chains, and polymers containing only anionic groups experience a significant decrease in adsorption capacity due to charge shielding effects; existing technologies that introduce nanomaterials mostly employ physical blending, but nanomaterials are prone to agglomeration in the alkaline environment of cement slurry, resulting in poor dispersion stability and difficulty in maintaining their effectiveness. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent and its preparation method.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent. Based on 100 parts by weight of deionized water, the raw materials for preparing the fluid loss reducing agent include: 7-12 parts of sulfonic acid monomers, 5-9 parts of amide monomers, 2-5 parts of lactam monomers, 1-3 parts of hydroxy ester monomers, 0.8-2.5 parts of zwitterionic monomers, 0.2-0.8 parts of carboxylated nanocellulose, 0.1-0.5 parts of vinylsilane hybrid crosslinking agent, 0.4-0.8 parts of redox initiation system, and 0.05-0.2 parts of chain transfer agent. The raw materials for preparing the fluid loss reducing agent also include a pH adjuster to adjust the pH of the system to 6.5-7.5.

[0006] Preferably, the sulfonic acid monomer is at least one of 2-acrylamido-2-methylpropanesulfonic acid and sodium vinyl sulfonate; the amide monomer is at least one of N,N-dimethylacrylamide and acrylamide; the lactam monomer is at least one of N-vinylcaprolactam and N-vinylpyrrolidone; the hydroxy ester monomer is at least one of hydroxyethyl methacrylate and hydroxyethyl acrylate; the zwitterionic monomer is methacryloyloxyethyl sulfobetaine; the chain transfer agent is at least one of mercaptoacetic acid and mercaptopropionic acid; and the pH adjuster is at least one of sodium hydroxide and sodium carbonate.

[0007] Preferably, based on 100 parts by weight of deionized water, the redox initiation system includes 0.2-0.4 parts of oxidant and 0.2-0.4 parts of reductant; the oxidant is at least one of ammonium persulfate and potassium persulfate; and the reductant is at least one of sodium bisulfite and sodium sulfite.

[0008] Preferably, the raw materials for preparing the carboxylated nanocellulose, by weight, include: 1.5-2.5 parts of nanocrystalline cellulose, 0.03-0.06 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, 0.15-0.30 parts of sodium bromide, 8-15 parts of sodium hypochlorite solution with an effective chlorine content of 10%-13%, and 200-300 parts of deionized water, wherein the nanocrystalline cellulose is used in the form of a suspension with a solid content of 8%-12%.

[0009] Preferably, the method for preparing the carboxylated cellulose nanoparticles includes the following steps: 1) Add the nanocrystalline cellulose suspension to deionized water and ultrasonically disperse it at 0~5℃ for 30~40 min, with an ultrasonic frequency of 30~40kHz and a power of 250~400W to obtain a uniform nanocrystalline cellulose suspension. 2) At 0~5℃, add 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide to the nanocrystalline cellulose suspension in sequence, and stir at 250~350r / min for 10~15min until completely dissolved; 3) Under stirring conditions at 0~5℃, add sodium hypochlorite solution dropwise to the system obtained in step 2) at a uniform rate over 25~40 min. During the dropwise addition, maintain the pH of the system at 10.0~10.5 with sodium hydroxide solution of concentration of 0.4~0.6mol / L. After the dropwise addition is completed, continue to stir the reaction at 20~25℃ for 4~6 h. 4) After the reaction is complete, add 10% sodium sulfite solution to terminate the reaction until the starch-potassium iodide test paper no longer turns blue, and then adjust the pH to 6.5-7.0 with 0.4-0.6 mol / L hydrochloric acid solution. 5) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 8000~10000 Da, dialyze with deionized water for 48~72 hours, and change the dialysate every 6~8 hours until the conductivity of the dialysate is lower than 5 μS / cm. 6) The dialysis suspension was dried under a vacuum of 0.08~0.09MPa and a temperature of 45~55℃ for 20~28h, and then ground to obtain carboxylated nanocellulose.

[0010] Preferably, the raw materials for preparing the vinylsilane hybrid crosslinking agent include vinyltriethoxysilane and deionized water, and the mass ratio of vinyltriethoxysilane to deionized water is 1:4 to 1:6.

[0011] The method for preparing the vinylsilane hybrid crosslinking agent is as follows: Deionized water is heated to 25~30℃, and the pH is adjusted to 3.5~4.5 with hydrochloric acid with a concentration of 0.08~0.12mol / L. Vinyltriethoxysilane is slowly added dropwise under stirring. After the addition is complete, the mixture is stirred at a speed of 250~350r / min for 2.5~3.5h to obtain an aqueous dispersion of vinylsilane hybrid crosslinking agent with an effective component content of 14%~20% vinyltriethoxysilane.

[0012] This invention also provides a method for preparing a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent, comprising the following steps: S1. Add sulfonic acid monomers, amide monomers, lactam monomers, hydroxy ester monomers and zwitterionic monomers to 100 parts by weight of deionized water, stir at 250~350 r / min for 15~20 min, and then adjust the pH of the system to 6.5~7.5 with a sodium hydroxide solution with a concentration of 18~22 wt%. S2. Carboxylated nanocellulose is prepared into a deionized aqueous solution with a mass fraction of 1%~2%, and slowly added to the solution obtained in step S1. It is ultrasonically dispersed for 25~40 min, and then a vinylsilane hybrid crosslinking agent is added. The mixture is stirred at a speed of 250~350 r / min for 15~20 min to obtain a premixed solution. S3. Transfer the premixed solution to a four-necked flask equipped with a stirrer, thermometer, reflux condenser and dropping funnel. After deoxygenation, heat to 55~70℃, then add chain transfer agent and stir at 250~350r / min for 5~10min. S4. Under nitrogen protection, prepare initiator solutions with a mass fraction of 2% to 3% for both oxidant and reducing agent, and then slowly add them dropwise to the reaction system obtained in step S3 through a dropping funnel. The dropping time is controlled at 40 to 70 minutes, and the reaction temperature is maintained at 55 to 70°C during the dropping process. After the dropping is completed, stir at a constant temperature at a speed of 250 to 350 r / min for 4 to 6 hours. S5. After the reaction is complete, the mixture is naturally cooled to 20~25℃ under stirring conditions to obtain a temperature- and salt-resistant oil well cement slurry dehydration agent.

[0013] Preferably, in step S2, the conditions for ultrasonic dispersion are: ultrasonic frequency 30~40kHz, power 250~400W.

[0014] Preferably, in step S3, the deoxygenation operation specifically involves introducing nitrogen gas for deoxygenation for 20-30 minutes.

[0015] The beneficial effects of this invention are as follows: Sulfonic acid monomers participate in polymer backbone formation, providing salt resistance; amide monomers participate in polymer backbone formation, improving the bonding ability between the polymer and cement particles; lactam monomers participate in polymer backbone formation, improving the thermal stability of the polymer; hydroxy ester monomers participate in polymer backbone formation, enhancing the interaction between the polymer and cement particles; the zwitterionic monomer methacryloyloxyethyl sulfobetaine participates in polymer backbone formation, and its positive and negative charged groups in its molecular structure have an anti-polyelectrolyte effect, causing the molecular chain to extend in a high-salt environment, significantly improving the polymer's hydrodynamic volume and salt adsorption resistance; carboxylated nanocellulose forms one-dimensional rigid rod-like structures. The structure is uniformly dispersed in the polymer system, filling the pores of the filter cake and improving its density. Numerous carboxyl groups on its surface can simultaneously form hydrogen bonds and electrostatic interactions with cement particles and polymer chains, enhancing system stability and structural integrity at high temperatures. A vinylsilane hybrid crosslinking agent is introduced into the polymer backbone through vinyl participation in free radical polymerization. The silanol groups generated by its hydrolysis further undergo condensation reactions to form Si-O-Si inorganic crosslinking bonds, ultimately constructing an organic-inorganic hybrid three-dimensional network structure. A redox initiator initiates the monomer polymerization reaction. A chain transfer agent regulates the polymer's molecular weight. A pH adjuster adjusts the system pH to 6.5–7.5 to ensure the smooth progress of the polymerization reaction.

[0016] Nanocrystalline cellulose serves as the reaction matrix, providing a one-dimensional nanoscale rigid rod-like structure; 2,2,6,6-tetramethylpiperidine-1-oxy radicals act as selective oxidation catalysts, catalyzing the oxidation of primary hydroxyl groups on the surface of nanocrystalline cellulose; sodium bromide acts as a co-catalyst, enhancing the reaction rate; sodium hypochlorite solution acts as an oxidant, providing active chlorine for the oxidation reaction; and deionized water acts as the reaction medium, dispersing the raw material components and ensuring that the oxidation reaction proceeds in a uniformly dispersed system.

[0017] Vinyltriethoxysilane is used as a reactant monomer to provide vinyl groups that can participate in polymerization and siloxane groups that can undergo hydrolysis and condensation. Deionized water is used as a reaction medium to disperse vinyltriethoxysilane. Hydrochloric acid is used to adjust the pH of the system to weakly acidic to promote the hydrolysis and condensation reaction of vinyltriethoxysilane. The reaction is carried out under stirring conditions to ensure that the hydrolysis and condensation of vinyltriethoxysilane is uniform, resulting in a water-dispersible oligomer containing vinyl and silanol groups. This oligomer can participate in subsequent polymerization reactions to form a cross-linked structure. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1: This embodiment provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent. Based on 100 parts by weight of deionized water, the raw materials for preparing the fluid loss reducing agent include: 7 parts of sulfonic acid monomers, 5 parts of amide monomers, 2 parts of lactam monomers, 1 part of hydroxy ester monomers, 0.8 parts of zwitterionic monomers, 0.2 parts of carboxylated nanocellulose, 0.1 parts of vinylsilane hybrid crosslinking agent, 0.2 parts of oxidant, 0.2 parts of reducing agent, and 0.05 parts of chain transfer agent. The raw materials for preparing the fluid loss reducing agent also include a pH adjuster to adjust the pH of the system to 6.5.

[0020] The sulfonic acid monomer is 2-acrylamido-2-methylpropanesulfonic acid; the amide monomer is N,N-dimethylacrylamide; the lactam monomer is N-vinylcaprolactam; the hydroxy ester monomer is hydroxyethyl methacrylate; the zwitterionic monomer is methacryloyloxyethyl sulfobetaine; the chain transfer agent is mercaptoacetic acid; the pH adjuster is sodium hydroxide. The oxidizing agent is ammonium persulfate; the reducing agent is sodium bisulfite.

[0021] The raw materials for preparing carboxylated nanocellulose, by weight, include: 1.5 parts of nanocrystalline cellulose, 0.03 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, 0.15 parts of sodium bromide, 8 parts of sodium hypochlorite solution with an effective chlorine content of 10%, and 200 parts of deionized water. The nanocrystalline cellulose is used in the form of a suspension with a solid content of 8%.

[0022] The preparation method of carboxylated cellulose nanoparticles includes the following steps: 1) Add the nanocrystalline cellulose suspension to deionized water and ultrasonically disperse it for 30 min at 0℃ with an ultrasonic frequency of 30 kHz and a power of 250 W to obtain a uniform nanocrystalline cellulose suspension. 2) At 0℃, 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide were added sequentially to the nanocrystalline cellulose suspension, and the mixture was stirred at 250 r / min for 10 min until completely dissolved. 3) Under stirring conditions at 0℃, sodium hypochlorite solution was added dropwise to the system obtained in step 2) at a uniform rate over 25 min. During the dropwise addition, the pH of the system was maintained at 10.0 using sodium hydroxide solution with a concentration of 0.4 mol / L. After the dropwise addition was completed, the reaction was stirred at 20℃ for 4 h. 4) After the reaction is complete, add 10% sodium sulfite solution to terminate the reaction until the starch potassium iodide test paper no longer turns blue, and then adjust the pH to 6.5 with 0.4 mol / L hydrochloric acid solution. 5) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 8000 Da, dialyze with deionized water for 48 hours, and change the dialysate every 6 hours until the conductivity of the dialysate is lower than 5 μS / cm. 6) The dialysis suspension was dried for 20 hours under a vacuum of 0.08 MPa and a temperature of 45°C, and then ground to obtain carboxylated nanocellulose.

[0023] The raw materials for preparing the vinylsilane hybrid crosslinking agent include vinyltriethoxysilane and deionized water, with a mass ratio of vinyltriethoxysilane to deionized water of 1:4.

[0024] The preparation method of vinylsilane hybrid crosslinking agent is as follows: Deionized water is heated to 25°C, and the pH is adjusted to 3.5 with hydrochloric acid with a concentration of 0.08 mol / L. Vinyltriethoxysilane is slowly added dropwise under stirring. After the addition is complete, the mixture is stirred at a speed of 250 r / min for 2.5 h to obtain an aqueous dispersion of vinylsilane hybrid crosslinking agent with an effective component content of 14%.

[0025] This embodiment also provides a method for preparing a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent, comprising the following steps: S1. Add sulfonic acid monomers, amide monomers, lactam monomers, hydroxy ester monomers and zwitterionic monomers to 100 parts by weight of deionized water, stir at 250 r / min for 15 min, and then adjust the pH of the system to 6.5 with 18 wt% sodium hydroxide solution. S2. Carboxylated nanocellulose was prepared into a 1% deionized aqueous solution and slowly added to the solution obtained in step S1. It was ultrasonically dispersed for 25 min at a frequency of 30 kHz and a power of 250 W. Then, a vinylsilane hybrid crosslinking agent was added and stirred at 250 r / min for 15 min to obtain a premix. S3. Transfer the premixed solution to a four-necked flask equipped with a stirrer, thermometer, reflux condenser and dropping funnel, purge with nitrogen to remove oxygen for 20 min, heat to 55°C, then add chain transfer agent and stir at 250 r / min for 5 min. S4. Under nitrogen protection, prepare initiator solutions with a mass fraction of 2% for both oxidant and reducing agent, and then slowly add them dropwise to the reaction system obtained in step S3 through a dropping funnel. The dropping time is controlled at 40 min, and the reaction temperature is maintained at 55℃ during the dropping process. After the dropping is completed, stir at a constant temperature of 250 r / min for 4 h. S5. After the reaction is complete, the mixture is naturally cooled to 20°C under stirring conditions to obtain a temperature- and salt-resistant oil well cement slurry dehydration reducer.

[0026] Example 2: This embodiment provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent. Based on 100 parts by weight of deionized water, the raw materials for preparing the fluid loss reducing agent include: 12 parts of sulfonic acid monomers, 9 parts of amide monomers, 5 parts of lactam monomers, 3 parts of hydroxy ester monomers, 2.5 parts of zwitterionic monomers, 0.8 parts of carboxylated nanocellulose, 0.5 parts of vinylsilane hybrid crosslinking agent, 0.4 parts of oxidant, 0.4 parts of reducing agent, and 0.2 parts of chain transfer agent. The raw materials for preparing the fluid loss reducing agent also include a pH adjuster to adjust the pH of the system to 7.5.

[0027] The sulfonic acid monomer is sodium vinyl sulfonate; the amide monomer is acrylamide; the lactam monomer is N-vinylpyrrolidone; the hydroxy ester monomer is hydroxyethyl acrylate; the zwitterionic monomer is methacryloyloxyethyl sulfobetaine; the chain transfer agent is mercaptopropionic acid; the pH adjuster is sodium hydroxide. The oxidizing agent is potassium persulfate; the reducing agent is sodium sulfite.

[0028] The raw materials for preparing carboxylated nanocellulose, by weight, include: 2.5 parts of nanocrystalline cellulose, 0.06 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, 0.3 parts of sodium bromide, 15 parts of sodium hypochlorite solution with an effective chlorine content of 13%, and 300 parts of deionized water. The nanocrystalline cellulose is used in the form of a suspension with a solid content of 12%.

[0029] The preparation method of carboxylated cellulose nanoparticles includes the following steps: 1) Add the nanocrystalline cellulose suspension to deionized water and ultrasonically disperse it at 5°C for 40 min at an ultrasonic frequency of 40 kHz and a power of 400 W to obtain a uniform nanocrystalline cellulose suspension. 2) At 5°C, 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide were added sequentially to the nanocrystalline cellulose suspension, and the mixture was stirred at 350 r / min for 15 min until completely dissolved. 3) Under stirring conditions at 5℃, sodium hypochlorite solution was added dropwise to the system obtained in step 2) at a uniform rate over 40 min. During the dropwise addition, the pH of the system was maintained at 10.5 using sodium hydroxide solution with a concentration of 0.6 mol / L. After the dropwise addition was completed, the reaction was stirred at 25℃ for 6 h. 4) After the reaction is complete, add a 10% sodium sulfite solution to terminate the reaction until the starch-potassium iodide test paper no longer turns blue, and then adjust the pH to 7.0 with a 0.6 mol / L hydrochloric acid solution. 5) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 10000 Da, dialyze with deionized water for 72 hours, and change the dialysate every 8 hours until the conductivity of the dialysate is lower than 5 μS / cm. 6) The dialysis suspension was dried for 28 hours under a vacuum of 0.09 MPa and a temperature of 55 °C, and then ground to obtain carboxylated nanocellulose.

[0030] The raw materials for preparing the vinylsilane hybrid crosslinking agent include vinyltriethoxysilane and deionized water, with a mass ratio of vinyltriethoxysilane to deionized water of 1:6.

[0031] The preparation method of vinylsilane hybrid crosslinking agent is as follows: Deionized water is heated to 30°C, and the pH is adjusted to 4.5 with hydrochloric acid with a concentration of 0.12 mol / L. Vinyltriethoxysilane is slowly added dropwise under stirring. After the addition is complete, the mixture is stirred at a speed of 350 r / min for 3.5 h to obtain an aqueous dispersion of vinylsilane hybrid crosslinking agent with an effective component content of 20%.

[0032] This embodiment also provides a method for preparing a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent, comprising the following steps: S1. Add sulfonic acid monomers, amide monomers, lactam monomers, hydroxy ester monomers and zwitterionic monomers to 100 parts by weight of deionized water, stir at 350 r / min for 20 min, and then adjust the pH of the system to 7.5 with a 22 wt% sodium hydroxide solution. S2. Carboxylated nanocellulose was prepared into a 2% deionized aqueous solution and slowly added to the solution obtained in step S1. It was ultrasonically dispersed for 40 min at a frequency of 40 kHz and a power of 400 W. Then, a vinylsilane hybrid crosslinking agent was added and stirred at 350 r / min for 20 min to obtain a premix. S3. Transfer the premixed solution to a four-necked flask equipped with a stirrer, thermometer, reflux condenser and dropping funnel, purge with nitrogen to remove oxygen for 30 min, heat to 70°C, then add chain transfer agent and stir at 350 r / min for 10 min. S4. Under nitrogen protection, prepare initiator solutions with a mass fraction of 3% for both oxidant and reducing agent, and then slowly add them dropwise to the reaction system obtained in step S3 through a dropping funnel. The dropping time is controlled at 70 min, and the reaction temperature is maintained at 70℃ during the dropping process. After the dropping is completed, stir at a constant temperature of 350 r / min for 6 h. S5. After the reaction is complete, the mixture is naturally cooled to 25°C under stirring conditions to obtain a temperature- and salt-resistant oil well cement slurry dehydration reducer.

[0033] Example 3: This embodiment provides a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent. Based on 100 parts by weight of deionized water, the raw materials for preparing the fluid loss reducing agent include: 9 parts of sulfonic acid monomers, 7 parts of amide monomers, 3.5 parts of lactam monomers, 2 parts of hydroxy ester monomers, 1.6 parts of zwitterionic monomers, 0.5 parts of carboxylated nanocellulose, 0.3 parts of vinylsilane hybrid crosslinking agent, 0.3 parts of oxidant, 0.3 parts of reducing agent, and 0.12 parts of chain transfer agent. The raw materials for preparing the fluid loss reducing agent also include a pH adjuster to adjust the pH of the system to 7.0.

[0034] The sulfonic acid monomer is 2-acrylamido-2-methylpropanesulfonic acid; the amide monomer is N,N-dimethylacrylamide; the lactam monomer is N-vinylcaprolactam; the hydroxy ester monomer is hydroxyethyl methacrylate; the zwitterionic monomer is methacryloyloxyethyl sulfobetaine; the chain transfer agent is mercaptoacetic acid; the pH adjuster is sodium hydroxide. The oxidizing agent is ammonium persulfate; the reducing agent is sodium bisulfite.

[0035] The raw materials for preparing carboxylated nanocellulose, by weight, include: 2 parts nanocrystalline cellulose, 0.04 parts 2,2,6,6-tetramethylpiperidine-1-oxy free radical, 0.22 parts sodium bromide, 11 parts sodium hypochlorite solution with an effective chlorine content of 12%, and 250 parts deionized water. The nanocrystalline cellulose is used in the form of a suspension with a solid content of 10%.

[0036] The preparation method of carboxylated cellulose nanoparticles includes the following steps: 1) Add the nanocrystalline cellulose suspension to deionized water and ultrasonically disperse it at 3°C ​​for 35 min at an ultrasonic frequency of 35 kHz and a power of 320 W to obtain a uniform nanocrystalline cellulose suspension. 2) At 2℃, 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide were added sequentially to the nanocrystalline cellulose suspension, and the mixture was stirred at 300 r / min for 12 min until completely dissolved. 3) Under stirring conditions at 2℃, sodium hypochlorite solution was added dropwise to the system obtained in step 2) at a uniform rate over 32 min. During the dropwise addition, the pH of the system was maintained at 10.2 using a 0.5 mol / L sodium hydroxide solution. After the dropwise addition was completed, the reaction was stirred at 22℃ for 5 h. 4) After the reaction is complete, add 10% sodium sulfite solution to terminate the reaction until the starch potassium iodide test paper no longer turns blue, and then adjust the pH to 6.8 with 0.5 mol / L hydrochloric acid solution. 5) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 9000 Da, dialyze with deionized water for 60 h, and change the dialysate every 7 h until the conductivity of the dialysate is lower than 5 μS / cm. 6) The dialysis suspension was dried for 24 hours under a vacuum of 0.085 MPa and a temperature of 50 °C, and then ground to obtain carboxylated nanocellulose.

[0037] The raw materials for preparing the vinylsilane hybrid crosslinking agent include vinyltriethoxysilane and deionized water, with a mass ratio of vinyltriethoxysilane to deionized water of 1:5.

[0038] The preparation method of vinylsilane hybrid crosslinking agent is as follows: Deionized water is heated to 28°C, and the pH is adjusted to 4.0 with hydrochloric acid with a concentration of 0.1 mol / L. Vinyltriethoxysilane is slowly added dropwise under stirring. After the addition is completed, the mixture is stirred at a speed of 300 r / min for 3 h to obtain an aqueous dispersion of vinylsilane hybrid crosslinking agent with an effective component content of 17%.

[0039] This embodiment also provides a method for preparing a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent, comprising the following steps: S1. Add sulfonic acid monomers, amide monomers, lactam monomers, hydroxy ester monomers and zwitterionic monomers to 100 parts by weight of deionized water, stir at 300 r / min for 18 min, and then adjust the pH of the system to 7.0 with a 20 wt% sodium hydroxide solution. S2. Carboxylated nanocellulose was prepared into a 1.5% deionized aqueous solution and slowly added to the solution obtained in step S1. The solution was ultrasonically dispersed for 32 min at a frequency of 35 kHz and a power of 320 W. Then, a vinylsilane hybrid crosslinking agent was added and stirred at 300 r / min for 18 min to obtain a premix. S3. Transfer the premixed solution to a four-necked flask equipped with a stirrer, thermometer, reflux condenser and dropping funnel, purge with nitrogen to remove oxygen for 25 min, heat to 62℃, then add chain transfer agent and stir at 300 r / min for 8 min. S4. Under nitrogen protection, prepare initiator solutions with a mass fraction of 2.5% for both oxidant and reducing agent, and then slowly add them dropwise to the reaction system obtained in step S3 through a dropping funnel. The dropping time is controlled at 55 min, and the reaction temperature is maintained at 62℃ during the dropping process. After the dropping is completed, stir at a constant temperature of 300 r / min for 5 h. S5. After the reaction is complete, the mixture is naturally cooled to 22°C under stirring conditions to obtain a temperature- and salt-resistant oil well cement slurry dehydration agent.

[0040] Comparative Example 1: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that carboxylated nanocellulose is not added.

[0041] Comparative Example 2: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that no vinylsilane hybrid crosslinking agent is added.

[0042] Comparative Example 3: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that the zwitterionic monomer methacryloyloxyethyl sulfobetaine is not added.

[0043] Comparative Example 4: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that the lactam monomer N-vinylcaprolactam is replaced with an equal mass of N-vinylpyrrolidone.

[0044] Comparative Example 5: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that the hydroxy ester monomer hydroxyethyl methacrylate is not added, but is replaced with an equal mass of N,N-dimethylacrylamide.

[0045] Comparative Example 6: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that the vinylsilane hybrid crosslinking agent is replaced with an equal mass of unhydrolyzed vinyltriethoxysilane monomer.

[0046] Comparative Example 7: A temperature- and salt-resistant oil well cement slurry dehydration agent and its preparation method are disclosed. The only difference between this agent and Example 3 is that the chain transfer agent mercaptoacetic acid is not added.

[0047] The water loss reducing agents obtained in Examples 1-3 and Comparative Examples 1-7 were tested for the following properties: 1. Cement slurry preparation method Cement slurry preparation was performed in accordance with GB / T 19139-2012 "Test Methods for Cement in Oil Wells". The cement slurry formulations for different test conditions are as follows: 90℃ Freshwater Cement Slurry Formula: 500g Grade G oil well cement, 220g fresh water (water-cement ratio 0.44), water loss reducer added at 4.0% of cement mass (BWOC), and tributyl phosphate defoamer 0.2g.

[0048] 150℃ Freshwater Cement Slurry Formula: 500g Grade G oil well cement, 175g silica fume (35% of cement mass, used to prevent strength degradation at temperatures above 110℃), 220g fresh water, 5.5% (BWOC) of water loss reducer by cement mass, and 0.2g defoamer.

[0049] Formula for 200℃ freshwater cement slurry: 500g of G-grade oil well cement, 200g of silica fume (40% of cement mass), 220g of fresh water, 7.0% of cement mass as water loss reducer (BWOC), and 0.2g of defoamer.

[0050] Formula for 130℃ semi-saturated brine cement slurry: 500g of G-grade oil well cement, 175g of silica fume, 220g of semi-saturated brine (sodium chloride content 18wt%), 6.0% (BWOC) of water loss reducer by cement mass, and 0.2g of defoamer.

[0051] Formula for 130℃ saturated brine cement slurry: 500g of G-grade oil well cement, 175g of silica fume, 220g of saturated brine (sodium chloride content 35wt%), 7.0% (BWOC) of water loss reducer by cement mass, and 0.2g of defoamer.

[0052] 2. API Water Loss Test Method The test was conducted according to GB / T 19139-2012 Oil Well Cement Test Methods. A high-temperature, high-pressure fluid loss meter was used, with test temperatures of 90℃, 150℃, and 200℃, a pressure difference of 6.9 MPa, and a test time of 30 min. The volume of filtrate within 30 min was recorded, multiplied by 2 to convert to the standard 30-min API fluid loss, expressed in mL / 30 min.

[0053] 3. Test methods for free liquid and sedimentation stability The test was conducted according to GB / T 19139-2012, "Test Methods for Cement in Oil Wells". The prepared cement slurry was poured into the slurry cup of an atmospheric pressure thickener and allowed to stand for 2 hours under the corresponding test temperature conditions. After removal, the volume of the upper free liquid was measured, and the free liquid volume was expressed as a percentage of the total cement slurry volume. Density samples were taken from the top and bottom of the cement slurry column and measured; the density difference was expressed in g / cm³. 3 This indicates that it is used to evaluate settlement stability.

[0054] 4.24h compressive strength test method The test was conducted according to GB / T 19139-2012 Oil Well Cement Test Method. The prepared cement slurry was poured into a standard mold and placed in a high-temperature, high-pressure curing autoclave. The mold was then cured for 24 hours at the corresponding test temperature and 20.7 MPa pressure. The cement stone sample was removed and subjected to constant loading at a pressure testing machine until the sample failed. The maximum failure load was recorded, and the compressive strength was calculated using formula (1): P=F / A......(1) In the formula: P represents compressive strength, in MPa; F is the maximum destructive load, N; A is the sample bearing area, in mm. 2 .

[0055] 5. Thickening Time Test Method The test was conducted according to GB / T 19139-2012, "Test Methods for Cement in Oil Wells". A high-temperature, high-pressure thickener was used, with the test conditions being the corresponding test temperature and 65 MPa pressure. The prepared cement slurry was poured into the thickener cup and placed inside the thickener. Continuous testing was performed under the predetermined temperature and pressure conditions. The time taken for the cement slurry to reach a consistency of 100 Bc was recorded as the thickening time, expressed in minutes.

[0056] The results are shown in Tables 1, 2 and 3.

[0057] Table 1. Performance test results of freshwater cement slurry at 90℃ Table 2. Performance test results of freshwater cement slurry at 150℃ Table 3. Performance test results of 130℃ brine cement slurry and 200℃ freshwater cement slurry Using Example 3 as the control group, the performance differences and causes of Comparative Examples 1-7 are analyzed as follows: Comparative Example 1 (without carboxylated nanocellulose): Under fresh water conditions at 90℃, the API water loss increased from 24 mL / 30 min to 48 mL / 30 min (an increase of 100%), the free liquid content increased from 0.02% to 0.20%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.026 g / cm³ 3 The 24-hour compressive strength decreased from 20.2 MPa to 15.2 MPa (a decrease of 24.8%); under 150℃ fresh water conditions, the API water loss increased from 28 mL / 30 min to 56 mL / 30 min (an increase of 100%), the thickening time decreased from 230 min to 170 min (a decrease of 26.1%), the free liquid increased from 0.01% to 0.22%, and the compressive strength decreased from 19.5 MPa to 14.5 MPa (a decrease of 25.6%); under 200℃ fresh water conditions, A The water loss of PI increased from 35 mL / 30 min to 70 mL / 30 min (an increase of 100%), while the compressive strength decreased from 17.0 MPa to 13.0 MPa (a decrease of 23.5%). Under semi-saturated brine conditions at 130℃, the water loss of API increased from 30 mL / 30 min to 64 mL / 30 min (an increase of 113.3%). Under saturated brine conditions at 130℃, the water loss of API increased from 34 mL / 30 min to 74 mL / 30 min (an increase of 117.6%). Carboxylated nanocellulose has a nanoscale rigid rod-like structure, which can form a physical entanglement network in cement slurry filter cake to block nanoscale filtration channels. Its surface carboxyl groups can be converted into carboxylate groups in alkaline cement slurry environment, providing electrostatic repulsion to enhance the dispersion stability of cement particles. At the same time, the carboxyl groups can complex with calcium ions on the surface of cement particles to form chemical anchors. Without this component, the filter cake relies solely on polymer film formation to control water loss, resulting in the loss of the nanoscale physical clogging effect and a significant decrease in filter cake density. Simultaneously, the lack of electrostatic dispersion and calcium ion complexation anchoring provided by carboxyl groups deteriorates the dispersion stability of cement particles, leading to a significant increase in free liquid volume and density difference, and a decrease in sedimentation stability. Under high temperature and high salinity conditions, the collapse of the polymer hydration layer and ion penetration intensify, making the filter cake structure more susceptible to damage. Consequently, the increase in water loss reaches as high as 117.6% under saturated saline conditions, and the compressive strength also shows a significant decrease.

[0058] Comparative Example 2 (without vinylsilane hybrid crosslinking agent): Under fresh water conditions at 90℃, the API water loss increased from 24 mL / 30 min to 46 mL / 30 min (an increase of 91.7%), the free liquid content increased from 0.02% to 0.19%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.024 g / cm³ 3 The compressive strength decreased from 20.2 MPa to 15.8 MPa (a decrease of 21.8%); under fresh water conditions at 150℃, the API water loss increased from 28 mL / 30 min to 53 mL / 30 min (an increase of 89.3%), the thickening time decreased from 230 min to 175 min (a decrease of 23.9%), the free liquid increased from 0.01% to 0.20%, and the compressive strength decreased from 19.5 MPa to 14.8 MPa (a decrease of 24.1%); under fresh water conditions at 200℃, the API... The water loss increased from 35 mL / 30 min to 65 mL / 30 min (an increase of 85.7%), and the compressive strength decreased from 17.0 MPa to 13.5 MPa (a decrease of 20.6%). Under semi-saturated brine conditions at 130℃, the API water loss increased from 30 mL / 30 min to 61 mL / 30 min (an increase of 103.3%). Under saturated brine conditions at 130℃, the API water loss increased from 34 mL / 30 min to 70 mL / 30 min (an increase of 105.9%). The vinylsilane hybrid crosslinking agent, through vinyl participation in free radical copolymerization, covalently introduces siloxane segments into the polymer backbone. In the alkaline environment of cement slurry, the silanol groups further hydrolyze and condense to form a Si-O-Si three-dimensional network. Simultaneously, it can react with the hydroxylated calcium sites on the surface of cement particles to form Si-O-Ca covalent bonds, anchoring the polymer film to the surface of the cement particles. Without this component, the polymer membrane has only a linear or slightly physically cross-linked structure, and the organic-inorganic hybrid cross-linked network cannot be formed. The structural rigidity and resistance to ion penetration of the filter cake are significantly weakened at high temperatures. At the same time, the lack of chemical bonding and anchoring between silanol groups and the cement surface reduces the adhesion strength of the polymer membrane under high temperature and high salinity conditions, resulting in an increase of more than 85% in water loss under various temperature and salinity conditions, and a decrease of 20.6% in compressive strength at 200℃.

[0059] Comparative Example 3 (without the addition of the zwitterionic monomer methacryloyloxyethyl sulfobetaine): Under fresh water conditions at 90℃, the API water loss increased from 24 mL / 30 min to 40 mL / 30 min (an increase of 66.7%), the free liquid content increased from 0.02% to 0.14%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.018 g / cm³ 3The compressive strength decreased from 20.2 MPa to 17.5 MPa (a decrease of 13.4%); under 150℃ fresh water conditions, the API water loss increased from 28 mL / 30 min to 46 mL / 30 min (an increase of 64.3%), the thickening time decreased from 230 min to 190 min (a decrease of 17.4%), the free liquid increased from 0.01% to 0.15%, and the compressive strength decreased from 19.5 MPa to 16.8 MPa (a decrease of 13.8%); under 200℃ fresh water conditions, the API... The water loss of API increased from 35 mL / 30 min to 46 mL / 30 min (an increase of 31.4%), and the compressive strength decreased from 17.0 MPa to 15.5 MPa (a decrease of 8.8%). Under semi-saturated brine conditions at 130℃, the water loss of API increased from 30 mL / 30 min to 62 mL / 30 min (an increase of 106.7%). Under saturated brine conditions at 130℃, the water loss of API increased from 34 mL / 30 min to 80 mL / 30 min (an increase of 135.3%). Methacryloxyethyl sulfobetaine molecules contain both quaternary ammonium cations and sulfonic acid anions, exhibiting an anti-polyelectrolyte effect in brine environments: high concentrations of free ions shield the attraction of positive and negative charges within the zwitterionic units, restoring the extended conformation of the molecular chains, thickening the hydration layer, and compensating for the decreased adsorption capacity of pure anionic polymers in brine due to charge shielding. Without this component, the polymer in saturated brine relies solely on the sulfonic acid groups of 2-acrylamido-2-methylpropanesulfonic acid to resist salting out. Sodium ions significantly compress the electric double layer of cement particles, weakening electrostatic repulsion and causing the polymer adsorption layer to loosen, leading to a sharp increase in water loss. Therefore, the salt sensitivity of this comparative example is extremely significant: the increase in water loss in saturated brine reaches as high as 135.3%, far exceeding the 66.7% under freshwater conditions, fully demonstrating the unique contribution of zwitterionic monomers in brine environments. Under freshwater conditions, due to the absence of charge shielding effect, polymer adsorption is relatively stable, and the increase in water loss is limited.

[0060] Comparative Example 4 (N-vinylcaprolactam, a lactam monomer, was replaced with an equal mass of N-vinylpyrrolidone): Under fresh water conditions at 90℃, the API water loss increased from 24 mL / 30 min to 38 mL / 30 min (an increase of 58.3%), the free liquid content increased from 0.02% to 0.11%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.015 g / cm³ 3The compressive strength decreased from 20.2 MPa to 16.8 MPa (a decrease of 16.8%); under fresh water conditions at 150℃, the API water loss increased from 28 mL / 30 min to 50 mL / 30 min (an increase of 78.6%), the thickening time decreased from 230 min to 200 min (a decrease of 13.0%), the free liquid increased from 0.01% to 0.14%, and the compressive strength decreased from 19.5 MPa to 15.5 MPa (a decrease of 20.5%); under fresh water conditions at 200℃, the API... The water loss of API increased from 35 mL / 30 min to 62 mL / 30 min (an increase of 77.1%), while the compressive strength decreased from 17.0 MPa to 14.5 MPa (a decrease of 14.7%). Under semi-saturated brine conditions at 130℃, the API water loss increased from 30 mL / 30 min to 50 mL / 30 min (an increase of 66.7%). Under saturated brine conditions at 130℃, the API water loss increased from 34 mL / 30 min to 56 mL / 30 min (an increase of 64.7%). In the seven-membered lactam ring structure of N-vinylcaprolactam, the alkyl substituents around the amide carbonyl group are more numerous, resulting in greater steric hindrance. This effectively hinders the nucleophilic attack of hydroxide ions on the amide carbonyl group in high-temperature alkaline cement slurry, thus exhibiting superior hydrolytic stability and significantly inhibiting the ring-opening breakage of the amide bond in the polymer backbone, maintaining the integrity of the molecular structure. In contrast, the five-membered lactam ring of N-vinylpyrrolidone has less steric hindrance, making the amide carbonyl group more susceptible to OH groups. - The attack of the component leads to hydrolytic degradation, resulting in a decrease in polymer molecular weight and performance degradation. After the replacement of this component, although the five-membered ring structure provides some thermal stability, its hydrolytic stability in the ultra-high temperature range is significantly weaker than that of the seven-membered ring structure. Therefore, this comparative example shows a clear temperature dependence: the increase in water loss in fresh water at 200℃ is 77.1%, while the increase in water loss in fresh water at 90℃ is 58.3%, and the performance difference is greater at higher temperatures. In the temperature range of 130℃ and below, the performance difference between the two is relatively small, further confirming that N-vinylcaprolactam plays a dominant role in the ultra-high temperature range.

[0061] Comparative Example 5 (hydroxyethyl methacrylate monomer without added hydroxy ester, replaced by an equal mass of N,N-dimethylacrylamide): Under fresh water conditions at 90℃, the API water loss increased from 24 mL / 30 min to 42 mL / 30 min (an increase of 75.0%), the free liquid content increased from 0.02% to 0.13%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.017 g / cm³ 3The 24-hour compressive strength decreased from 20.2 MPa to 14.5 MPa (a decrease of 28.2%); under 150℃ fresh water conditions, the API water loss increased from 28 mL / 30 min to 49 mL / 30 min (an increase of 75.0%), the thickening time decreased from 230 min to 195 min (a decrease of 15.2%), the free liquid increased from 0.01% to 0.15%, and the compressive strength decreased from 19.5 MPa to 14.2 MPa (a decrease of 27.2%); under 200℃ fresh water conditions, API water loss increased from 35 mL / 30 min to 46 mL / 30 min (an increase of 31.4%), while compressive strength decreased from 17.0 MPa to 12.8 MPa (a decrease of 24.7%). Under semi-saturated brine conditions at 130℃, API water loss increased from 30 mL / 30 min to 54 mL / 30 min (an increase of 80.0%). Under saturated brine conditions at 130℃, API water loss increased from 34 mL / 30 min to 58 mL / 30 min (an increase of 70.6%). Hydroxyethyl methacrylate (HHME) side chains contain active hydroxyl groups, which can form hydrogen bonds with hydroxyl groups on the surface of cement particles in the low to medium temperature range, enhancing the polymer's anchoring effect on cement. Simultaneously, it can promote the nucleation and growth of CSH gel in the early stages of cement hydration, which is beneficial for the early strength development of cement paste. The absence of this component, replaced by N,N-dimethylacrylamide, weakened the hydrogen bond anchoring effect in the low-to-medium temperature range, resulting in the loss of the nucleation-promoting effect in the early stage of cement hydration. This led to a 28.2% decrease in compressive strength in 90℃ fresh water after 24 hours, the most significant decrease among all comparative examples. At the same time, due to the lack of hydrogen bond bonding between hydroxyl groups and cement particles, the adsorption coverage of the polymer on the cement surface decreased, and the water loss increased significantly under all conditions.

[0062] Comparative Example 6 (the vinylsilane hybrid crosslinking agent was replaced with an equal mass of unhydrolyzed vinyltriethoxysilane monomer): Under fresh water conditions at 90°C, the API water loss increased from 24 mL / 30 min to 42 mL / 30 min (an increase of 75.0%), the free liquid content increased from 0.02% to 0.17%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.023 g / cm³ 3The compressive strength decreased from 20.2 MPa to 15.5 MPa (a decrease of 23.3%); under fresh water conditions at 150℃, the API water loss increased from 28 mL / 30 min to 48 mL / 30 min (an increase of 71.4%), the thickening time decreased from 230 min to 180 min (a decrease of 21.7%), the free liquid increased from 0.01% to 0.20%, and the compressive strength decreased from 19.5 MPa to 14.8 MPa (a decrease of 24.1%); under fresh water conditions at 200℃, the API... The water loss of API increased from 35 mL / 30 min to 55 mL / 30 min (an increase of 57.1%), and the compressive strength decreased from 17.0 MPa to 13.2 MPa (a decrease of 22.4%). Under semi-saturated brine conditions at 130℃, the API water loss increased from 30 mL / 30 min to 55 mL / 30 min (an increase of 83.3%). Under saturated brine conditions at 130℃, the API water loss increased from 34 mL / 30 min to 64 mL / 30 min (an increase of 88.2%). When vinyltriethoxysilane monomers are added directly to the polymerization system without pre-hydrolysis, they are difficult to disperse uniformly and participate in copolymerization due to their poor water solubility. Furthermore, the unpre-condensed monomers undergo excessively rapid hydrolysis and condensation in alkaline cement slurry, failing to effectively form a uniform organic-inorganic hybrid crosslinked network, and are prone to self-polymerization or phase separation. Therefore, although this comparative example introduced silane components, it failed to form covalent bonds with the polymer matrix and a Si-O-Si three-dimensional network structure. The reaction between the silanol groups and the hydroxylated calcium sites on the cement surface was also uneven, resulting in significantly insufficient crosslinking density and anchoring strength of the polymer film. The increase in water loss in fresh water at 200℃ reached 57.1%, and the increase in water loss in saturated brine was as high as 88.2%, indicating that the crosslinking and anchoring efficiency of unhydrolyzed silane under harsh conditions is far lower than that of pre-hydrolyzed hybrid crosslinking agents.

[0063] Comparative Example 7 (without chain transfer agent thioglycolic acid): Under 90℃ fresh water conditions, the API water loss increased from 24 mL / 30 min to 52 mL / 30 min (an increase of 116.7%), the free liquid content increased from 0.02% to 0.24%, and the density difference increased from 0.006 g / cm³. 3 Increased to 0.030 g / cm³ 3The compressive strength decreased from 20.2 MPa to 15.0 MPa (a decrease of 25.7%); under fresh water conditions at 150℃, the API water loss increased from 28 mL / 30 min to 62 mL / 30 min (an increase of 121.4%), the thickening time decreased from 230 min to 158 min (a decrease of 31.3%), the free liquid content increased from 0.01% to 0.27%, and the compressive strength decreased from 19.5 MPa to 13.8 MPa (a decrease of 29.2%); under fresh water conditions at 200℃, the API... The water loss of API increased from 35 mL / 30 min to 64 mL / 30 min (an increase of 82.9%), and the compressive strength decreased from 17.0 MPa to 12.5 MPa (a decrease of 26.5%). Under semi-saturated brine conditions at 130℃, the API water loss increased from 30 mL / 30 min to 66 mL / 30 min (an increase of 120.0%). Under saturated brine conditions at 130℃, the API water loss increased from 34 mL / 30 min to 72 mL / 30 min (an increase of 111.8%). Chain transfer agents regulate polymer molecular weight through chain transfer reactions, preventing excessively high molecular weight from causing abnormally high cement paste viscosity. Without this component, chain growth during polymerization is uncontrolled, resulting in excessively high product molecular weight. High molecular weight polymer chains produce severe bridging and flocculation effects in the cement paste, leading to deterioration of the cement paste's rheological properties, abnormally high viscosity, and a significant decrease in the dispersion stability of cement particles. This is most evident in the most significant increases in free liquid volume and density difference among the comparative examples. Meanwhile, the adsorption conformation of polymers with excessively high molecular weight on the surface of cement particles is too extended. Although the steric hindrance effect is strong, the film density is reduced and the filter cake structure is loose. As a result, the water loss increases by more than 80% under all conditions, and the increase is as high as 121.4% under 150℃ fresh water conditions. The compressive strength decreases by 29.2%.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A temperature- and salt-resistant oil well cement slurry fluid loss reducing agent, characterized in that, Based on 100 parts by weight of deionized water, the raw materials for preparing the water loss reducing agent include: 7-12 parts of sulfonic acid monomers, 5-9 parts of amide monomers, 2-5 parts of lactam monomers, 1-3 parts of hydroxy ester monomers, 0.8-2.5 parts of zwitterionic monomers, 0.2-0.8 parts of carboxylated nanocellulose, 0.1-0.5 parts of vinylsilane hybrid crosslinking agent, 0.4-0.8 parts of redox initiation system, and 0.05-0.2 parts of chain transfer agent; the raw materials for preparing the water loss reducing agent also include a pH adjuster, used to adjust the pH of the system to 6.5-7.

5.

2. The temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 1, characterized in that, The sulfonic acid monomer is at least one of 2-acrylamido-2-methylpropanesulfonic acid and sodium vinyl sulfonate; the amide monomer is at least one of N,N-dimethylacrylamide and acrylamide; the lactam monomer is at least one of N-vinylcaprolactam and N-vinylpyrrolidone; the hydroxy ester monomer is at least one of hydroxyethyl methacrylate and hydroxyethyl acrylate; the zwitterionic monomer is methacryloyloxyethyl sulfobetaine; the chain transfer agent is at least one of mercaptoacetic acid and mercaptopropionic acid; and the pH adjuster is at least one of sodium hydroxide and sodium carbonate.

3. The temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 1, characterized in that, Based on 100 parts by weight of deionized water, the redox initiation system includes 0.2-0.4 parts of oxidant and 0.2-0.4 parts of reductant; the oxidant is at least one of ammonium persulfate and potassium persulfate; the reductant is at least one of sodium bisulfite and sodium sulfite.

4. The temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 1, characterized in that, The raw materials for preparing the carboxylated nanocellulose, by weight, include: 1.5-2.5 parts of nanocrystalline cellulose, 0.03-0.06 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, 0.15-0.30 parts of sodium bromide, 8-15 parts of sodium hypochlorite solution with an effective chlorine content of 10%-13%, and 200-300 parts of deionized water. The nanocrystalline cellulose is used in the form of a suspension with a solid content of 8%-12%.

5. The temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 4, characterized in that, The preparation method of the carboxylated cellulose nanoparticles includes the following steps: 1) Add the nanocrystalline cellulose suspension to deionized water and ultrasonically disperse it at 0~5℃ for 30~40 min, with an ultrasonic frequency of 30~40kHz and a power of 250~400W to obtain a uniform nanocrystalline cellulose suspension. 2) At 0~5℃, add 2,2,6,6-tetramethylpiperidine-1-oxy free radical and sodium bromide to the nanocrystalline cellulose suspension in sequence, and stir at 250~350r / min for 10~15min until completely dissolved; 3) Under stirring conditions at 0~5℃, add sodium hypochlorite solution dropwise to the system obtained in step 2) at a uniform rate over 25~40 min. During the dropwise addition, maintain the pH of the system at 10.0~10.5 with sodium hydroxide solution of concentration of 0.4~0.6mol / L. After the dropwise addition is completed, continue to stir the reaction at 20~25℃ for 4~6 h. 4) After the reaction is complete, add 10% sodium sulfite solution to terminate the reaction until the starch-potassium iodide test paper no longer turns blue, and then adjust the pH to 6.5-7.0 with 0.4-0.6 mol / L hydrochloric acid solution. 5) Transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 8000~10000 Da, dialyze with deionized water for 48~72 hours, and change the dialysate every 6~8 hours until the conductivity of the dialysate is lower than 5 μS / cm. 6) The dialysis suspension was dried under vacuum of 0.08~0.09MPa and temperature of 45~55℃ for 20~28h, and then ground to obtain carboxylated nanocellulose.

6. The temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 1, characterized in that, The raw materials for preparing the vinylsilane hybrid crosslinking agent include vinyltriethoxysilane and deionized water, and the mass ratio of vinyltriethoxysilane to deionized water is 1:4 to 1:

6. The method for preparing the vinylsilane hybrid crosslinking agent is as follows: Deionized water is heated to 25~30℃, and the pH is adjusted to 3.5~4.5 with hydrochloric acid with a concentration of 0.08~0.12mol / L. Vinyltriethoxysilane is slowly added dropwise under stirring. After the addition is complete, the mixture is stirred at a speed of 250~350r / min for 2.5~3.5h to obtain an aqueous dispersion of vinylsilane hybrid crosslinking agent with an effective component content of 14%~20% vinyltriethoxysilane.

7. A method for preparing a temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Add sulfonic acid monomers, amide monomers, lactam monomers, hydroxy ester monomers and zwitterionic monomers to 100 parts by weight of deionized water, stir at 250~350 r / min for 15~20 min, and then adjust the pH of the system to 6.5~7.5 with a sodium hydroxide solution with a concentration of 18~22 wt%. S2. Prepare a deionized aqueous solution with a mass fraction of 1%~2% by carboxylated nanocellulose, slowly add it to the solution obtained in step S1, and ultrasonically disperse it for 25~40 min. Then add a vinylsilane hybrid crosslinking agent and stir at a speed of 250~350 r / min for 15~20 min to obtain a premixed solution. S3. Transfer the premixed solution to a four-necked flask equipped with a stirrer, thermometer, reflux condenser and dropping funnel. After deoxygenation, heat to 55~70℃, then add chain transfer agent and stir at 250~350r / min for 5~10min. S4. Under nitrogen protection, prepare initiator solutions with a mass fraction of 2% to 3% for both oxidant and reducing agent, and then slowly add them dropwise to the reaction system obtained in step S3 through a dropping funnel. The dropping time is controlled at 40 to 70 minutes, and the reaction temperature is maintained at 55 to 70°C during the dropping process. After the dropping is completed, stir at a constant temperature at a speed of 250 to 350 r / min for 4 to 6 hours. S5. After the reaction is complete, the mixture is naturally cooled to 20~25℃ under stirring conditions to obtain a temperature- and salt-resistant oil well cement slurry dehydration agent.

8. The preparation method of the temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 7, characterized in that, In step S2, the conditions for ultrasonic dispersion are: ultrasonic frequency 30~40kHz, power 250~400W.

9. The preparation method of the temperature- and salt-resistant oil well cement slurry fluid loss reducing agent according to claim 7, characterized in that, In step S3, the deoxygenation operation specifically involves introducing nitrogen gas for 20-30 minutes.